Influences on safety of intrapartum electronic fetal heart rate monitoring practices: a scoping review - Cathy Winter; Mary Dixon-Woods; Isla Kuhn; Guillaume Lamé; Elisa Liberati; Jenni Burt; Sarah Kelly; Alice Egerton; Tim J Draycott; Harry Kyriacou; Kathryn Jones; Harry Dunn; et al. (BMJ Open)
Objectives Suboptimal intrapartum electronic fetal heart rate monitoring using cardiotocography has remained a persistent problem (EFM-CTG). We aimed to identify the range of influences on the safety of using EFM-CTG in practice.Design Scoping review to identify influences related to the practice of intrapartum EFM.Data sources MEDLINE, Embase, CINAHL, Web of Science, Scopus, British Nursing Index, Cochrane Library, from 1 January 2001 to 25 August 2024, and grey literature.Eligibility criteria Articles that reported potential influences on the clinical practice of intrapartum EFM-CTG in hospital-based intrapartum maternity care settings, including primary studies, secondary analyses, reviews, reports, conference abstracts and investigations relevant to maternity and obstetrics, in English. Evaluations of technological modifications to traditional EFM-CTG monitoring and analysis were excluded.Data extraction and synthesis We extracted influences on EFM-CTG from the included studies. Findings were synthesised using a best-fit framework approach, structured using an existing 19-domain framework of contributory factors for patient safety incidents in hospitals.Results 142 articles and 14 reports were included. Our synthesis identified influences on EFM practice across all 19 domains of the contributory factors framework, including those relating to cognitive, social and organisational factors and interactions between professional work and tools used for fetal monitoring.Conclusion Reducing avoidable harm associated with electronic fetal monitoring requires a systems approach based on a sound understanding of the full range of influences on practice.